KEANEKARAGAMAN DAN KESAMARATAAN REPTIL PADA BEBERAPA TIPE HABITAT DI UNIVERSITAS LAMPUNG - Naradia Ayu Kartika; Bainah Sari Dewi; Rusita Rusita; Yulia Rahma Fitriana (University of Lampung, 2021)
Reptile are one of the fauna that make up ecosystems for inhabitants of aquatic, terrestrial to arboreal. This research was conducted to determine the diversity of Reptile in different habitat types : 1) ponds, 2) agroforestry, and 3) rice fields in the University of Lampung. The data was collected using the Visual Encounter Survey (VES) method which was modified by the time search method. Identification is done by using a field guide book. Data analysis was performed using the Shannon-Wiener species diversity and the evenness index. At the University of Lampung, there were 97 amphibians consisting of 6 species belonging to 6 families. The diversity and uniformity level of the three habitats, namely pond habitat H'= 1.28 (low) and J= 0.86 , agroforestry habitat H'= 1.28 and J= 0.92 , and rice research H'=1.06 and J = 0.96 the diversity in both area are moderate and the evenness are stable.